Comparison of Six Dilute Russell Viper Venom Time Lupus Anticoagulant Screen/Confirm Assay Kits - McGlasson, David L.; Fritsma, George A. (Seminars in Thrombosis and Hemostasis, 2013)
Background The normalized dilute Russell viper venom time (DRVVT) ratio provides a robust assay methodology for lupus anticoagulant (LA) detection.Objectives We evaluated six normalized DRVVT LA screen and confirm systems for inter-method consistency. Reagents were purchased from Diagnostica Stago, Inc. (Parsippany, NJ); Precision BioLogic Inc. (Halifax, Nova Scotia, Canada); Siemens Healthcare Inc. (Deerfield, IL); TCoag (Parsippany, NJ); Instrumentation Laboratories (Bedford, MA); and Sekisui Diagnostics (Pfungstadt, Germany).Methods For all assays, we employed the STA-R Evolution automated coagulometer, adhering to manufacturers' instructions. LA-positive and LA-negative plasma controls were purchased from Diagnostica Stago and pooled normal plasma (PNP) was purchased from Precision BioLogic. We computed the mean of the reference interval (MRI) and action limits for all kits using LA-negative aliquots from locally sourced normal subjects (n = 42). We then assayed locally sourced LA-positive plasmas (n = 43) and using analysis of variance compared uncorrected screen/confirm ratios and screen/confirm ratios that were normalized using MRI and mean PNP results.Results The grand mean action limit, MRI + 3 SD, derived from the local normal plasmas, was 1.2, confirming the manufacturers' recommended limits; however, limits must be locally computed. The all-sample p value was less than 0.001, indicating heterogeneity among ratios. When Sekisui ratios were excluded, the p value was 0.14, thus indicating that this method introduced the major difference among methods. Mean screen/confirm ratios computed from LA-positive specimens were 1.91 to 2.04 for reagent systems other than Sekisui, which instead yielded a mean ratio of 1.198, indicating that this method was relatively insensitive to LA. A negative bias was recorded by two lots from the Sekisui system for LA-positive specimens. Screen/confirm ratios from combined LA-positive and LA-negative samples generated a combined range of 1.59 to 1.67 for all reagents except Sekisui, which instead yielded 1.09. The within-run percent coefficient of variation (CV%) was less than 5.0% using all samples. Between-run CV% using Diagnostica Stago LA-positive and LA-negative controls was less than 5.5%.Conclusions DRVVT screen/confirm ratios discriminate between LA-positive and LA-negative samples and generally provide acceptable reproducibility. Ratio results may vary among reagent–instrument combinations. In this study, normalization added little to the clinical result interpretation.
Keywords: dilute Russell viper venom time; lupus anticoagulant; antiphospholipid antibody; LA-sensitive partial thromboplastin time; mean of the reference interval; normalization